2022
DOI: 10.1371/journal.pone.0264994
|View full text |Cite
|
Sign up to set email alerts
|

Positive attitudes towards COVID-19 vaccines: A cross-country analysis

Abstract: COVID-19 severely impacted world health and, as a consequence of the measures implemented to stop the spread of the virus, also irreversibly damaged the world economy. Research shows that receiving the COVID-19 vaccine is the most successful measure to combat the virus and could also address its indirect consequences. However, vaccine hesitancy is growing worldwide and the WHO names this hesitancy as one of the top ten threats to global health. This study investigates the trend in positive attitudes towards va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 42 publications
4
29
0
9
Order By: Relevance
“…29 The declining support from the public posed a global challenge for policymakers to rely on vaccination to end the pandemic. 28,30 The government should prepare early to maintain public support for vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…29 The declining support from the public posed a global challenge for policymakers to rely on vaccination to end the pandemic. 28,30 The government should prepare early to maintain public support for vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies explored the characteristics of the vaccine discourse on social media during the pandemic ( 18 21 ), though only few studies ( 22 ) investigated the impact of the pandemic on the vaccine-related discourse, comparing its characteristics before and during COVID-19. Our objective was to understand how the Italian conversation about vaccines on Twitter changed during the first phase of the pandemic, in terms of vaccine stance, involved actors and dominant narratives, compared to the months immediately preceding the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In the large international study, authors investigated variables related to having a positive attitude as factors that could potentially increase the uptake of vaccines. They found that the following variables could improve people’s attitudes towards vaccines: better information about the COVID-19 vaccines in general, and especially information related to the safety and side effects of vaccines; increased trust in governments in conducting the vaccine rollout; and handling procurement and capacity issues [ 43 ].…”
Section: Discussionmentioning
confidence: 99%